Lung surfactants and different contributions to thin film stability. Issue 41 (26th August 2015) - Hermans, Eline; Saad Bhamla, M.; Kao, Peter; Fuller, Gerald G.; Vermant, Jan
Abstract : In the present work, we investigate the mechanisms affecting the stability of surfactant-laden thin films during spreading, using drainage flows from a hemispherical dome. Three commercial lung surfactant replacements Survanta, Curosurf and Infasurf, along with the phospholipid dipalmitoylphosphatidylcholine (DPPC), are used. Abstract : The surfactant lining the walls of the alveoli in the lungs increases pulmonary compliance and prevents collapse of the lung at the end of expiration. In premature born infants, surfactant deficiency causes problems, and lung surfactant replacements are instilled to facilitate breathing. These pulmonary surfactants, which form complex structured fluid–fluid interfaces, need to spread with great efficiency and once in the alveolus they have to form a thin stable film. In the present work, we investigate the mechanisms affecting the stability of surfactant-laden thin films during spreading, using drainage flows from a hemispherical dome. Three commercial lung surfactant replacements Survanta, Curosurf and Infasurf, along with the phospholipid dipalmitoylphosphatidylcholine (DPPC), are used. The surface of the dome can be covered with human alveolar epithelial cells and experiments are conducted at the physiological temperature. Drainage is slowed down due to the presence of all the different lung surfactant replacements and therefore the thin films show enhanced stability. However, a scaling analysis combined with visualization experiments demonstrates that different mechanisms are involved. For Curosurf and Infasurf, Marangoni stresses are essential to impart stability and interfacial shear rheology does not play a role, in agreement with what is observed for simple surfactants. Survanta, which was historically the first natural surfactant used, is rheologically active. For DPPC the dilatational properties play a role. Understanding these different modes of stabilization for natural surfactants can benefit the design of effective synthetic surfactant replacements for treating infant and adult respiratory disorders.